Political Communication and the Enforcement of Covid- 19 Rules in South Africa - AARON TSHIDZUMBA; LUSANDA JUTA (African Journal of Governance and Development, 2021)
Since the outbreak of the COVID-19 pandemic, several countries have attempted to respond via the introduction and adoption of strict and punitive measures to those breaking the covid-19 protocols. Relying on secondary and primary sources of data collection, this paper interrogates the various communication media that were used in sensitizing the citizenry in South Africa and their impact on enforcement as well as compliance to COVID-19 protocols. Regardless of the political dynamics and political distrust that characterize the state-citizen relations within the country, this study observes that to a reasonable extent, a uniform pattern of disseminating information both among government and private owned news sources created more awareness about the increasing spread of covid-19 and this was due to the perceived threat the pandemic posed to entire nation. Apart from the fact that this apparent uniformity in sensitization supported the enforcement of basic covid-19 protocols, it has sustained the level of awareness and compliance amidst the second wave. Therefore, beyond the COVID-19 pandemic, this study concludes that there is greater need for synergy between state and private owned media platforms in the overall interest of the country.